Reconstruction of the Achilles Tendon and Overlying Soft Tissue by Free Composite Anterolateral Thigh Flap with Vascularized Fascia Lata - Houtmeyers, Philippe; Opsomer, Dries; Van Landuyt, Koenraad; Monstrey, Stanislas (Journal of Reconstructive Microsurgery, 2012)
Segmental loss of the Achilles tendon with overlying soft tissue and skin defect remains a complex reconstructive challenge. Successful reconstruction combines tendon repair with coverage of the defect by soft tissue flaps, creating an entity that meets up to three predetermined goals: (1) approaching preinjury functionality, (2) resisting shearing forces, and (3) achieving an esthetic result. From June 2009 to June 2011, our center submitted six patients to a one-stage procedure correcting the Achilles tendon using a composite free anterolateral thigh (ALT) flap with vascularized fascia lata. The flap sizes ranged from 5 to 8 cm in width and 16 to 20 cm in length and all flaps included vascularized fascia lata which was rolled to serve as an Achilles tendon. After reconstruction our patients showed good functional results, these patients could walk, climb stairs, and tiptoe again without support. Moreover, normal footwear could be worn. A free composite ALT flap with vascularized fascia lata is a reliable option for coverage of Achilles tendon and overlying soft tissue defects, even in elderly patients.
Keywords: soft tissue defect; Achilles tendon; reconstruction; anterolateral thigh (ALT) flap; fascia lata